2018
DOI: 10.1093/nar/gky1232
|View full text |Cite
|
Sign up to set email alerts
|

Hydrophobicity drives the systemic distribution of lipid-conjugated siRNAs via lipid transport pathways

Abstract: Efficient delivery of therapeutic RNA beyond the liver is the fundamental obstacle preventing its clinical utility. Lipid conjugation increases plasma half-life and enhances tissue accumulation and cellular uptake of small interfering RNAs (siRNAs). However, the mechanism relating lipid hydrophobicity, structure, and siRNA pharmacokinetics is unclear. Here, using a diverse panel of biologically occurring lipids, we show that lipid conjugation directly modulates siRNA hydrophobicity. When administered in vivo, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
80
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(84 citation statements)
references
References 53 publications
4
80
0
Order By: Relevance
“…ORNst showed a two-fold higher uptake in liver (8416 ng/mg tissue), in spleen (4012 ng/mg tissue) and lung (174 ng/mg tissue), and a slightly reduced accumulation in kidney. These findings are again consistent with reports that siRNAs conjugated to hydrophobic fatty acids are transported to the liver at the expense of kidney (26). ORNch showed seven-fold higher levels in liver (34150 ng/mg tissue), a two-fold increase in spleen (5412 ng/mg tissue) and a 60% decrease in kidney compared to ORN1; the presence of ORNch in lung tissue was below accurate detection.…”
Section: Distribution and Metabolism Of Fech Ssos In Mouse Tissues Ansupporting
confidence: 91%
See 1 more Smart Citation
“…ORNst showed a two-fold higher uptake in liver (8416 ng/mg tissue), in spleen (4012 ng/mg tissue) and lung (174 ng/mg tissue), and a slightly reduced accumulation in kidney. These findings are again consistent with reports that siRNAs conjugated to hydrophobic fatty acids are transported to the liver at the expense of kidney (26). ORNch showed seven-fold higher levels in liver (34150 ng/mg tissue), a two-fold increase in spleen (5412 ng/mg tissue) and a 60% decrease in kidney compared to ORN1; the presence of ORNch in lung tissue was below accurate detection.…”
Section: Distribution and Metabolism Of Fech Ssos In Mouse Tissues Ansupporting
confidence: 91%
“…This study of splice-switching oligonucleotide conjugates complements recent investigations of the pharmacokinetic and pharmacodynamic properties of antisense and siRNA conjugates (26,27). The results reinforce the notion that increased delivery does not necessarily translate to improved potency.…”
Section: Introductionsupporting
confidence: 74%
“…Beyond the linker length and composition, the optimization of a particular amphiphilic drug also includes the amphiphilic modification that tunes the overall hydrophilic/lipophilic balance. For example, lipid composition and hydrophobicity have been shown to control the protein binding and biodistribution of lipid‐conjugate siRNA . Taken together, the above examples demonstrated the structures and physicochemical properties of amphiphilic drugs are highly tunable and can be tailored for targeted drug delivery.…”
Section: The Design Principles Of Self‐delivery Amphiphilic Drugsmentioning
confidence: 92%
“…Since lipid molecules exhibit strong affinity toward albumin and lipoproteins, lipid‐drug conjugates are widely used to hijack the trafficking pathways of serum proteins. The affinity and specificity of protein binding are primarily determined by the structures and hydrophobicity of the lipid …”
Section: The Design Principles Of Self‐delivery Amphiphilic Drugsmentioning
confidence: 99%
“…In contrast, association with HDL or apolipoprotein E promotes uptake into peripheral tissues via SR-BI. While the majority of work with cho-lesterol-siRNA conjugates was directed toward hepatic delivery, recent work demonstrated that cholesterol conjugation can deliver siRNA to muscle and other extrahepatic tissues in mice (60,61).…”
Section: Promoting Plasma Protein Interaction and Peripheral Tissue Dmentioning
confidence: 99%